THE TMEFF2 TUMOR SUPPRESSOR MODULATES INTEGRIN EXPRESSION, RHOA ACTIVATION AND MIGRATION OF PROSTATE CANCER CELLS - Chen, Xiaofei (2014)
Cell adhesion and migration play important roles in physiological and pathological states, including embryonic development and cancer invasion and metastasis. The type I transmembrane protein with epidermal growth factor and two follistatin motifs 2 (TMEFF2) is expressed mainly in brain and prostate and its expression is deregulated in prostate cancer. We have previously shown that TMEFF2 can function as a tumor suppressor by inhibiting cell migration and invasion of prostate cells. However, the molecular mechanisms involved in this inhibition are not clear. In this study we demonstrate that TMEFF2 affects cell adhesion and migration of prostate cancer cells and that this effect correlates with changes in integrin expression and RhoA activation. Deletion of a 13 basic-rich amino acid region in the cytoplasmic domain of TMEFF2 prevented these effects. Overexpression of TMEFF2 reduced cell attachment and migration on vitronectin and caused a concomitant decrease in RhoA activation, stress fiber formation and expression of αv, β1 and β3 integrin subunits. Conversely, TMEFF2 interference in 22Rv1 prostate cancer cells resulted in increased integrin expression. Results obtained with a double TRAMP/TMEFF2 transgenic mouse also indicated that TMEFF2 expression reduced integrin expression in the mouse prostate. In summary, the data presented here indicate an important role of TMEFF2 in regulating cell adhesion and migration that involves integrin signaling and is mediated by its cytoplasmic domain.